EFFECT OF WORKLOAD ON NURSES PERFORMANCE WITH WORK STRESS AS AN INTERVENING VARIABLE IN VIOLA MOTHER AND CHILD HOSPITAL - Pradana, Tito Wahyu; Ni Nyoman Sawitri; Adi Wibowo Noor Fikri (IJESM Indonesian Journal of Economics and Strategic Management, 2024)
The hospital is a sector engaged in the health sector to provide good service to patients. Viola Mother and Child Hospital which generally focuses on childbirth and obstetrical and child health care. The good and bad of a hospital can be seen in its performance which is also considered in the workload and work stress of nurses, if the workload is heavy and causes work stress then performance will decrease, and vice versa if the workload is low and there is no work stress then performance will increase. The population and sample in this study are nurses with quantitative research methods which collect data through interviews for the initial stage and questionnaires for the research stage. To analyze data through SMARTPLS 4.0 which can be used to see the path coefficient. The results of the study show that workload has a significant positive effect on performance (0.024<0.050 with Tstatistic 2.253>1.96), workload has a positive and significant effect on work stress (0.00<0.05), work stress has a significant and positive effect on performance (0.022<0.05 with tstatistic 2.294>1.96), and workload has a significant positive effect on nurse performance through work stress (0.022<0.05 with t statistics 2.284> 1.96).